THE STATE OF SPORTS AND RECREATIONAL TOURISM IN SARAJEVO CANTON IN THE PERIOD FROM 2011 TO 2021 - Amer Hodžić; Tarik Huremović (Sport Scientific And Practical Aspects, 2025)
The past decade within Bosnia and Herzegovina and thus in the Sarajevo Canton has shown that tourism has become a significant segment of the economy with a pronounced constant positive growth. He is one of the most important trump cards in economic development and positive recognition of the Sarajevo Canton and thus the state of Bosnia and Herzegovina. The paper analyzes the current state of sports and recreational tourism in Sarajevo Canton in the period from 2011 to 2021 and its possibilities through the sports and tourism offer. The research covered the administrative borders of Sarajevo Canton, which consists of 9 municipalities: Centar, Hadžići, Ilidža, Ilijaš, Novi Grad, Novo Sarajevo, Stari Grad, Trnovo and Vogošća. The paper analyzes the number of registered business entities (tourist units), the number of tourist arrivals (countries from which tourists come and by months of the year), the number of overnight stays, tourist arrivals individually or organized, the analysis of sports facilities and infrastructure for sports and tourism offer (mountaineering, sport climbing, athletic stadiums, swimming pools, bike and mountain bike trails, sports halls, golf courses, mountain walking trails, racetracks (equestrian sports), skating rinks, football stadiums and football fields, ski lifts, ski lifts, snowboard, point and toboggan runs, cross-country skiing, tennis courts). For the purposes of this research, a combination of: primary field research related to the state of sports facilities and sports infrastructure in the Sarajevo Canton as well as a secondary method of data collection through available official data, databases and reports of relevant public, private institutions, media, sports associations. By analyzing the situation and the results we have obtained, we can determine the direction for the development and expansion of services in terms of sports and recreational tourism in Sarajevo Canton. This does not require large investments, especially in the rural parts of Sarajevo Canton, which has all the benefits for further development of sports and recreational forms of offer in the direction of hiking, mountaineering, cycling, running, alpine, touring and Nordic skiing. Sarajevo Canton with its sports and competitive heritage as well as the existing specific sports infrastructure and facilities provide a great opportunity for tourism development and positive recognition of the Canton and the city of Sarajevo.